Cellulose hybrid aerogel for adsorbing micro-plastics as well as preparation method and application of cellulose hybrid aerogel
By extracting cellulose from agricultural solid waste and combining with vermiculite and polyethyleneimine, a stable three-dimensional network structure is formed, which improves the adsorption and recycling performance of cellulose aerogels, and solves the cellulose gas in the prior art The gel's shortcomings in adsorption performance and structural stability have achieved efficient removal of microplastics in water.
Patent Information
- Application Number
- CN202411343844.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cellulose aerogels have defects in adsorption performance and structural stability, and their recycling performance is insufficient, making it difficult to effectively remove microplastics in water.
By extracting cellulose from agricultural solid waste and processing with alkali urea solution under low temperature conditions, vermiculite and polyethyleneimine are added to form a stable three-dimensional network structure, which improves the adsorption and recycling performance of the aerogel.
The excellent adsorption performance and good recycling performance of cellulose hybrid aerogel on microplastics in water are achieved, and the problem of insufficient structural stability and adsorption performance of cellulose aerogel is solved.
Smart Images

Figure CN119161626A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogel preparation, and more specifically, to a cellulose hybrid aerogel for adsorbing microplastics, and a preparation method and application thereof. Background Art
[0002] Plastics are widely used in packaging, construction and other industries due to their low manufacturing cost, light weight, good flexibility and high electrical resistance. However, the widespread use and improper disposal of plastics have resulted in a large amount of plastic waste being left in the environment. After being irradiated by ultraviolet rays, oxidized and degraded, they are broken into small plastic particles, forming microplastics with a size of less than 5 mm. As a new type of pollutant, it has the characteristics of small particle size, large specific surface area and strong migration ability. It is also enriched in heavy metals and organic pollutants and can exist in every corner of the environment for a long time, making it difficult to remove. In particular, microplastics in water environments not only cause serious water pollution, but may also enter organisms including humans through ingestion, causing varying degrees of cell, tissue or organ damage to the organism. Therefore, how to quickly and efficiently remove microplastics from water is crucial to protecting the ecological environment and human health.
[0003] At present, microplastics are mainly removed through filtration, adsorption, coagulation / flocculation and biodegradation. Among them, the adsorption method is considered to be the most direct, effective and economical method due to its simple process and low cost. The preparation of adsorption materials with good adsorption performance is the key to the application of the adsorption method. Among the many adsorption materials, aerogel has attracted widespread attention due to its three-dimensional network structure, low density, high porosity, large specific surface area, and easy recycling.
[0004] In recent years, biomass aerogels have been favored by many researchers due to their biocompatibility, biodegradability and renewability. Cellulose is the most abundant, renewable and non-toxic natural biopolymer in nature, and is an ideal material for preparing biomass aerogels. As a major agricultural country, my country also produces a large amount of agricultural solid waste while producing crops. Agricultural solid wastes such as straw, rice straw, and corn cobs are widely distributed and have a large output, and are a rich source of cellulose. Extracting cellulose from agricultural solid waste can not only reduce the accumulation of agricultural solid waste, but also realize its resource utilization.
[0005] However, single cellulose aerogel adsorption materials generally have disadvantages such as low adsorption performance and poor structural stability, which seriously affect their application in adsorption. Therefore, improving the structural stability and adsorption performance of cellulose aerogel is an urgent problem to be solved in the preparation of high-performance aerogel adsorption materials.
[0006] Patent CN117143389A proposes a method for preparing a composite aerogel of microcrystalline cellulose / chitosan from bamboo shoot shells, which can cross-link microcrystalline cellulose and chitosan under the action of a cross-linking agent to form a composite aerogel. The composite aerogel presents a more stable three-dimensional cross-linked network structure, and its application in the treatment of microplastics in water bodies can produce electrostatic adsorption and physical adhesion with microplastics, greatly improving the removal effect of microplastics. However, it not only requires the cellulose extracted from bamboo shoot shells to be further hydrolyzed into microcrystalline cellulose, but also the cost of the raw material chitosan used is relatively high, which is not conducive to industrial production; in addition, its recycling performance still needs to be improved. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects and shortcomings of the existing cellulose aerogels that fail to take into account the adsorption performance, structural stability and recyclability at the same time, and to provide a method for preparing a cellulose hybrid aerogel.
[0008] Another object of the present invention is to provide a cellulose hybrid aerogel.
[0009] Another object of the present invention is to provide the use of the above-mentioned cellulose hybrid aerogel in adsorbing microplastics in water.
[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0011] The present invention provides a method for preparing a cellulose hybrid aerogel, comprising the following steps:
[0012] S1, extracting cellulose from agricultural solid waste, adding the cellulose to an alkaline urea solution, stirring and dispersing the cellulose, freezing the solution at a temperature not higher than -12°C, adding vermiculite after thawing, and stirring the solution to obtain a mixture;
[0013] S2, adding an organic amine and a cross-linking agent to the mixture, stirring evenly, standing to form a hydrogel, and freeze-drying to obtain the cellulose hybrid aerogel;
[0014] The organic amine is polyethyleneimine, and the mass ratio of the organic amine to cellulose is (7-12):8.
[0015] The present invention extracts cellulose from agricultural solid waste and uses it to prepare aerogel, thus realizing the resource utilization of agricultural solid waste. Then, an alkaline urea solution system is used to destroy the hydrogen bonds within and between cellulose molecules under low temperature conditions to dissolve the cellulose. Vermiculite with a layered structure is introduced to improve the structural stability of the aerogel by uniformly dispersing it in the cellulose aerogel; and vermiculite has a large specific surface area and contains hydroxyl groups in its crystal structure, which can form hydrogen bond interactions and is beneficial to adsorption. The added polyethyleneimine (PEI) is a water-soluble, strongly positively charged organic polymer, which contains a large number of amine groups on its main chain and side chains and has a large positive charge density. It can be used as a cellulose modifier to effectively improve the adsorption performance of the cellulose aerogel. Finally, a stable three-dimensional network structure is formed by cross-linking.
[0016] It should be noted that the selection and addition amount of organic amines have a significant effect on the adsorption performance of the material. When the addition amount of polyethyleneimine is insufficient, the adsorption performance needs to be improved; when the addition amount of polyethyleneimine is too large, due to the relatively large molecular weight of polyethyleneimine, it will lead to uneven distribution of the material, thus affecting the adsorption performance of the material. When low molecular weight organic amines, such as ethylenediamine or tetraethylenepentamine, are used, the prepared material has low stability and poor adsorption effect on microplastics. Experiments show that when the organic amine is polyethyleneimine and the mass ratio of organic amine to cellulose is (7-12):8, the prepared cellulose hybrid aerogel has excellent adsorption performance for microplastics in water and also has good recycling performance.
[0017] In some embodiments, in step S1, the mass ratio of cellulose to vermiculite is (5-8):(1-4), preferably 8:(1-3).
[0018] Controlling the ratio of cellulose and vermiculite is beneficial to the uniform dispersion of system components and improving the formability and structural stability of aerogel.
[0019] In some embodiments, the agricultural solid waste is selected from any one of rice straw, stalks, corn cobs or bagasse.
[0020] In some embodiments, the cellulose is extracted by subjecting agricultural solid waste to acid washing and alkali washing to remove lignin and hemicellulose impurities.
[0021] In some embodiments, in step S1, the process of extracting cellulose from agricultural solid waste includes:
[0022] 1) crushing agricultural solid waste into 50-200 meshes, placing it in a mixed aqueous solution containing sodium chlorite and glacial acetic acid, and performing acid treatment at 70-90°C;
[0023] 2) The material treated in step 1) is washed with water until the pH value is neutral, then placed in a sodium hydroxide solution, treated with alkali at 60-80° C., washed and dried to obtain cellulose powder.
[0024] Preferably, the cellulose is extracted by the following method:
[0025] The 50-200 mesh agricultural solid waste powder is placed in a mixed aqueous solution containing 3wt%-5wt% sodium chlorite and 2.5wt%-5wt% glacial acetic acid at a solid-liquid ratio of 1: (25-35), and reacted at 70-90° C. for 3-6 hours for acid treatment to remove lignin;
[0026] After the reaction is completed, the mixture is washed with deionized water until the pH value is neutral; then, the mixture is placed in a 4wt% to 6.5wt% sodium hydroxide solution and reacted at 60 to 80°C for 2 to 3 hours for alkaline treatment to remove hemicellulose;
[0027] After the reaction is completed, the cellulose powder is washed with deionized water to remove the reagent residue and ash, and then transferred to an oven for drying to obtain cellulose powder.
[0028] Agricultural solid waste contains cellulose, hemicellulose, lignin and some small molecules. After acid and alkali treatment, most of the lignin, hemicellulose and small molecules can be successfully removed, and the hydroxyl groups are fully exposed, so that cellulose with higher purity can be obtained.
[0029] In some embodiments, step S1 further includes pre-treatment of the vermiculite, including: sequentially subjecting the vermiculite to acid treatment and homogenization treatment, and obtaining the vermiculite with an average particle size of 10 to 20 μm.
[0030] Preferably, the vermiculite is processed by the following method:
[0031] Disperse 500-800 mesh vermiculite powder in 1-2 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:(25-35), react at 60-90°C for 2-6 hours, remove impurities after the reaction and wash with deionized water until the pH is neutral;
[0032] Then the dispersion is homogenized by a high-speed shearing machine and sheared at a speed of 10,000 to 15,000 rpm for 30 to 60 minutes. After impurities are removed, the dispersion is transferred to a high-speed centrifuge and centrifuged at a speed of 300 to 600 rpm for 30 to 45 minutes. The suspension after centrifugation is transferred to an oven for drying to obtain treated vermiculite powder.
[0033] The present invention can remove metal oxide compounds such as iron oxide compounds, aluminum oxide compounds and other impurities between vermiculite layers through acid treatment; homogenization treatment can make vermiculite particles more uniform and fine, which is helpful to improve dispersibility.
[0034] In some embodiments, in step S1, the components of the alkaline urea solution include: 5-10 wt % sodium hydroxide and 10-14 wt % urea.
[0035] In some embodiments, the solid-to-liquid ratio of the cellulose to the alkaline urea solution is 20-32 g / L.
[0036] In some embodiments, in step S2, the freezing treatment temperature is -18 to -12°C, and the freezing time is 12 to 15 hours.
[0037] In some embodiments, in step S2, the cross-linking agent is an alkylene oxide cross-linking agent or an aldehyde cross-linking agent, preferably epichlorohydrin or glutaraldehyde, more preferably epichlorohydrin.
[0038] When epichlorohydrin is used as a cross-linking agent in the present invention, epichlorohydrin undergoes a ring-opening reaction in an alkaline environment to open the epoxy ring, and the chloromethyl group at one end reacts with the hydroxyl group on the cellulose, and the epoxy group at the other end reacts with the amine group on the polyethyleneimine, thereby cross-linking the material to form a stable three-dimensional network structure.
[0039] The invention protects a cellulose hybrid aerogel, which is prepared by the preparation method of the cellulose hybrid aerogel.
[0040] The present invention protects the use of a cellulose hybrid aerogel in adsorbing microplastics in water.
[0041] Preferably, the microplastics are polystyrene (PS) microplastics.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The invention provides a method for preparing a cellulose hybrid aerogel, which adopts agricultural solid waste and vermiculite as raw materials, has a wide source and is green and environmentally friendly, thereby realizing the resource utilization of agricultural solid waste and vermiculite clay; the aerogel material has a simple preparation process, good stability and integrity, and is not easy to cause secondary pollution; the aerogel is used to adsorb and remove microplastics in water, can form hydrogen bonds and electrostatic adsorption with the microplastics, and not only has excellent adsorption performance, but also has good recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 These are physical pictures of the cellulose (CC) aerogel of comparative example 1 and the cellulose hybrid aerogel (PEI-CC / AEV) of example 1; wherein the left picture is the cellulose (CC) aerogel of comparative example 1, and the right picture is the cellulose hybrid aerogel (PEI-CC / AEV) of example 1.
[0045] Figure 2 It is a comparison diagram of the cellulose hybrid aerogel (PEI-CC / AEV) material of Example 1 immersed in pure water, acidic and alkaline solutions; among them, from left to right, the aerogel material is immersed in pure water, pH=1, and pH=13 solutions (the solutions in the same column have the same pH), and from top to bottom, it is immersed for 0h, 24h, and 48h (the immersion time in the same row is the same).
[0046] Figure 3 The infrared spectra (FTIR) of each component; wherein CC powder is extracted corn cob cellulose, CC aerogel is the cellulose aerogel of Comparative Example 1, and PEI-CC / AEV is the cellulose hybrid aerogel of Example 1.
[0047] Figure 4 is the X-ray diffraction pattern (XRD) of each component; wherein, VMT is expanded vermiculite, AEV is treated vermiculite, CC is the cellulose aerogel of Comparative Example 1, and PEI-CC / AEV is the cellulose hybrid aerogel of Example 1.
[0048] Figure 5 The graph shows the adsorption data of the cellulose hybrid aerogel (PEI-CC / AEV) of Example 1 and the cellulose (CC) aerogel of Comparative Example 1 to PS of different initial concentrations.
[0049] Figure 6 This is the recycling adsorption data diagram of the cellulose hybrid aerogel (PEI-CC / AEV) of Example 1. DETAILED DESCRIPTION
[0050] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0051] The raw materials used in the following examples and comparative examples are as follows:
[0052] Polyethyleneimine: MW70000, 50% aqueous solution; brand name E107080, manufacturer: Aladdin Company.
[0053] Vermiculite: average particle size is 800 mesh; batch number KLM230221, manufacturer is Kramar Company.
[0054] Example 1
[0055] A method for preparing a cellulose hybrid aerogel (PEI-CC / AEV) for adsorbing microplastics comprises the following steps:
[0056] 1) Extraction of cellulose from agricultural solid waste:
[0057] The purchased corn cob powder was passed through an 80-mesh sieve, and 10 g of the powder was uniformly dispersed in 300 mL of a mixed solution containing 4 wt% sodium chlorite and 3 wt% glacial acetic acid, and heated and stirred at 75°C for 5 h. After the reaction, it was cooled to room temperature and washed with deionized water until the pH was neutral. Subsequently, the above product was dispersed in 200 mL of a 6 wt% sodium hydroxide solution, heated and stirred at 70°C for 3 h. After the reaction, it was cooled to room temperature, washed with deionized water until the pH was neutral, and then transferred to an oven for drying to obtain corn cob cellulose (CC) powder.
[0058] 2) The vermiculite clay is treated with acid and homogenized in sequence:
[0059] 10 g of 800 mesh expanded vermiculite (VMT) was uniformly dispersed in 300 mL of 2 mol / L hydrochloric acid solution, heated and stirred at 80 ° C for 4 h, cooled to room temperature after the reaction, removed impurities and washed with deionized water until the pH was neutral; then homogenized by a high-speed shearing machine and sheared at 10000 rpm for 30 min; after removing impurities, the dispersion was transferred to a high-speed centrifuge and centrifuged at 300 rpm for 30 min. The suspension after centrifugation was transferred to an oven for drying to obtain treated vermiculite powder (AEV).
[0060] 3) Add cellulose to the alkaline urea solution, stir and disperse, and then pre-cool; after thawing, add clay powder and stir evenly to obtain a mixture:
[0061] 0.8 g of the corncob cellulose powder in step S1 is dispersed in 25 mL of alkaline urea solution, stirred evenly, and then ultrasonically dispersed for 20 minutes, and then transferred to a -18°C refrigerator for precooling for 12 hours; after the precooling is completed, the mixture is taken out and allowed to stand, thawed to room temperature, and then stirred evenly to obtain dissolved corncob cellulose; 0.3 g of the vermiculite powder treated in step S2 is added under stirring, and stirring is continued until the vermiculite powder is evenly dispersed, and then ultrasonically dispersed for 20 minutes to obtain a uniform corncob cellulose / vermiculite mixture.
[0062] 4) Adding polyethyleneimine and a cross-linking agent to the mixture in sequence, stirring and then standing to form a hydrogel, washing and removing impurities, and freeze-drying to obtain the cellulose hybrid aerogel that can be used to adsorb microplastics.
[0063] 0.9 g of polyethyleneimine was dissolved in 2 mL of deionized water, and the mixture was added dropwise to the mixture of step S3. After stirring at room temperature for 60 min, the mixture was ultrasonically dispersed for 10 min to obtain a uniform mixture. 3 mL of a cross-linking agent was slowly added under stirring, and epichlorohydrin was used as the cross-linking agent. After continuing to stir for 30 min, the mixture was transferred to a silica gel mold and allowed to stand for 12 h to cross-link and form a hydrogel. The formed hydrogel was fully soaked and washed with deionized water to remove the reagent residue. The hydrogel was then transferred to a refrigerator for freezing, and then dried in a vacuum freeze dryer for 24 h to obtain the cellulose hybrid aerogel material.
[0064] Wherein, the mass ratio of corncob cellulose, vermiculite and polyethyleneimine in this embodiment is 8:3:9.
[0065] Example 2
[0066] A method for preparing a cellulose hybrid aerogel for adsorbing microplastics, which is different from Example 1 in that the mass ratio of corncob cellulose, vermiculite and polyethyleneimine in this example is 8:3:7.
[0067] Example 3
[0068] A method for preparing a cellulose hybrid aerogel for adsorbing microplastics, which is different from Example 1 in that the mass ratio of corncob cellulose, vermiculite and polyethyleneimine in this example is 8:3:8.
[0069] Example 4
[0070] A method for preparing a cellulose hybrid aerogel for adsorbing microplastics, which is different from Example 1 in that the mass ratio of corncob cellulose, vermiculite and polyethyleneimine in this example is 8:3:10.
[0071] Example 5
[0072] A method for preparing a cellulose hybrid aerogel for adsorbing microplastics, which is different from Example 1 in that the mass ratio of corncob cellulose, vermiculite and polyethyleneimine in this example is 8:2:9.
[0073] Comparative Example 1
[0074] A method for preparing a corncob cellulose aerogel material is different from Example 1 in that vermiculite and polyethyleneimine are not added during the preparation process of this comparative example.
[0075] Comparative Example 2
[0076] A method for preparing a corncob cellulose aerogel material is different from Example 1 in that no crosslinking agent (epichlorohydrin) is added during the preparation process of this comparative example.
[0077] Comparative Example 3
[0078] A method for preparing a corncob cellulose aerogel material is different from Example 1 in that the mass ratio of corncob cellulose, vermiculite and polyethyleneimine in this comparative example is 8:3:5.
[0079] Comparative Example 4
[0080] A method for preparing a corncob cellulose aerogel material is different from Example 1 in that tetraethylenepentamine is used in this comparative example to replace polyethyleneimine.
[0081] Performance Testing
[0082] 1. Material forming test
[0083] The forming state of the aerogels of Examples 1 to 5 and Comparative Examples 1 to 4 in the silicone mold was observed; except for Comparative Example 2 which was still in a flowing state and did not form a hydrogel, the other hydrogel states were all good, indicating that the addition of the crosslinking agent had a great influence on whether the material was formed. Figure 1 As shown, the surface of the aerogel in Comparative Example 1 has many wrinkles and poor molding; the surface of the aerogel in Example 1 is smooth and the overall molding is good.
[0084] 2. Water stability test
[0085] The (PEI-CC / AEV) aerogel of Example 1 was immersed in pure water, acidic solution and alkaline solution for 48 hours respectively, and the stability of the material was roughly judged based on the changes in the appearance of the aerogel.
[0086] The results are as follows Figure 2 As shown, after the aerogel of Example 1 is immersed in pure water, acidic and alkaline solutions for 48 hours, the morphology of the aerogel does not change significantly and still has good integrity, indicating that the aerogel material can basically meet the test requirements.
[0087] 3. FTIR test
[0088] Fourier transform infrared spectrometer (FTIR) was used to characterize corncob cellulose (CC) powder, comparative example 1 (CC) aerogel, example 1 (PEI-CC / AEV) aerogel and the materials after absorbing PS.
[0089] The test results are as follows Figure 3 As shown in the FTIR image of the extracted corncob cellulose (CC) powder, 3396 cm -1 Corresponding to the bending vibration of -OH, 2899cm -1 Corresponding to the stretching vibration of CH bond, 1640, 1373cm -1 Corresponding to OH and CH bonds, 1000-1180cm -1The stretching and asymmetric vibrations corresponding to the CO, CC, and COC bonds indicated that cellulose was successfully extracted.
[0090] In the FTIR image of the corncob cellulose aerogel (CC aerogel) of Comparative Example 1, some peaks are weakened, which is caused by the dissolution of the corncob cellulose in the alkaline urea system and the breaking of hydrogen bonds.
[0091] In the FTIR spectrum of the aerogel (PEI-CC / AEV) of Example 1, 857 cm -1 A new characteristic peak appears at 1460 cm -1 Corresponding to the CN characteristic peak of polyethyleneimine, 3300cm -1 The -NH stretching peak in the region overlaps with the -OH peak of cellulose, indicating that vermiculite and polyethyleneimine were successfully introduced into cellulose aerogel.
[0092] In the FTIR image of the aerogel of Example 1 (PEI-CC / AEV) after adsorption of PS, four new characteristic peaks appeared: 3027 cm -1 Corresponding to the stretching vibration of aromatic CH bond, 1495 cm -1 Corresponding to the vibration of the benzene ring skeleton of PS, 758, 701 cm -1 The peaks at correspond to the CH bonds in the benzene ring. These peaks are typical peaks of PS microplastics, which can prove that the microplastics are successfully adsorbed onto the aerogel material.
[0093] 4. XRD test
[0094] The expanded vermiculite (VMT), the treated vermiculite (AEV), the (CC) aerogel of Comparative Example 1, and the (PEI-CC / AEV) aerogel of Example 1 were characterized and tested by X-ray diffractometer.
[0095] The test results are as follows Figure 4 As shown in the figure, it can be seen that the 001 crystal plane of the vermiculite powder (VMT) before treatment appears at 8.7°, and the 003 crystal plane appears at 26.6°; after acid treatment and homogenization treatment, the diffraction peak of the 001 crystal plane moves to a lower angle, and some diffraction peaks weaken or disappear, indicating that the crystal plane spacing of the treated vermiculite (AEV) increases, and a new large peak appears at 27.8°, indicating the formation of amorphous silica.
[0096] The aerogel of Comparative Example 1 (CC) exhibits a broad diffraction peak at 20.0°, corresponding to the 110 crystal plane of cellulose II.
[0097] In the XRD pattern of the aerogel of Example 1 (PEI-CC / AEV), compared with that of Comparative Example 1, the diffraction peak at 20.0° is broadened, which is caused by the successful introduction of vermiculite and polyethyleneimine into the cellulose aerogel.
[0098] 5. Adsorption test
[0099] The aerogel materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to adsorption tests.
[0100] The test method is as follows: the initial concentration of PS is set to 100 mg / L, the volume of the solution is 30 mL, 10 mg of the aerogel materials of Examples 1 to 5 and Comparative Examples 1 to 4 are weighed and added to the above solution, the oscillation frequency is set to 250 rpm, and the oscillation reaction is carried out at 25 ° C. for 3 hours. After the reaction is completed, the supernatant is taken, and the absorbance of the solution before and after adsorption is measured by a UV-visible spectrophotometer. The solution concentration and adsorption capacity are calculated by the standard curve. The results are shown in Table 1.
[0101] Table 1
[0102] Adsorption capacity mg / g Example 1 258.51 Example 2 193.50 Example 3 234.84 Example 4 217.14 Example 5 247.43 Comparative Example 1 18.80 Comparative Example 2 Unable to form Comparative Example 3 102.76 Comparative Example 4 122.98
[0103] The results show that increasing the dosage of polyethyleneimine modifier can improve the adsorption performance of aerogel materials, but when the dosage is too much, the adsorption performance will decrease.
[0104] When no vermiculite and polyethyleneimine were added in Comparative Example 1, its adsorption capacity for microplastics in water was extremely low; when no cross-linking agent was added in Comparative Example 2, aerogel could not be formed; when the amount of polyethyleneimine added in Comparative Example 3 was insufficient, its adsorption capacity for microplastics in water was low; and in Comparative Example 4, tetraethylenepentamine was used to replace polyethyleneimine, and the adsorption performance for microplastics in water was obviously insufficient, which proves that the use of polyethyleneimine is beneficial to improving material stability and enhancing the adsorption effect on microplastics.
[0105] 6. Adsorption test at different initial concentrations
[0106] The aerogel of Example 1 (PEI-CC / AEV) and the aerogel of Comparative Example 1 (CC) were subjected to adsorption tests at different initial concentrations.
[0107] The test method is as follows: set the initial PS concentration to 50-300 mg / L, the solution volume to 30 mL, weigh 10 mg of the aerogel materials of Example 1 and Comparative Example 1 respectively and add them to the above solution, set the oscillation frequency to 250 rpm, and oscillate at 25 ° C for 3 h. After the reaction is completed, take the supernatant, measure the absorbance of the solution before and after adsorption using a UV-visible spectrophotometer, and calculate the solution concentration and adsorption capacity using the standard curve. The test results are as follows: Figure 5 shown.
[0108] from Figure 5 It can be seen that under different initial concentration conditions, the adsorption capacity of PEI-CC / AEV aerogel is much higher than that of CC aerogel, indicating that the prepared cellulose hybrid aerogel material has good adsorption performance for PS microplastics.
[0109] 7. Recycling test
[0110] The aerogel material of Example 1 (PEI-CC / AEV) was tested for recycling.
[0111] The test method is as follows: the initial concentration of PS is set to 100 mg / L, the volume of the solution is 30 mL, 10 mg of the aerogel material of Example 1 is weighed and added to the above solution, the oscillation frequency is set to 250 rpm, and the oscillation reaction is carried out at 25 ° C for 3 hours. After the reaction, the supernatant is taken, and the absorbance of the solution before and after adsorption is measured by a UV-visible spectrophotometer. The solution concentration and adsorption capacity are calculated by the standard curve. The measured adsorption capacity is the first utilization; then the aerogel material and the microplastic solution are separated from the solid and liquid, and DMF is used to regenerate them after being collected. After freeze-drying, the regenerated aerogel material is used for the next round of adsorption test under the same adsorption test conditions, and so on. This test examines the utilization performance five times; the test results are as follows Figure 6 shown.
[0112] from Figure 6 It can be seen that the adsorption capacity of PEI-CC / AEV aerogel for PS is 258.51 mg / g when it is used for the first time. As the number of times of use increases, the adsorption capacity gradually decreases. After four adsorption cycles, the adsorption capacity is 184.46 mg / g, reaching more than 70% of the initial adsorption capacity. This shows that the cellulose hybrid aerogel material prepared by the present invention has good structural stability and good recycling performance.
[0113] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a cellulose hybrid aerogel, characterized in that: The steps include: S1, extracting cellulose from agricultural solid waste, adding the cellulose to an alkaline urea solution, stirring and dispersing the cellulose, freezing the solution at a temperature not higher than -12°C, adding vermiculite after thawing, and stirring the solution to obtain a mixture; S2, adding an organic amine and a cross-linking agent to the mixture, stirring evenly, standing to form a hydrogel, and freeze-drying to obtain the cellulose hybrid aerogel; The organic amine is polyethyleneimine, and the mass ratio of the organic amine to cellulose is (7-12):
8.
2. The method for preparing the cellulose hybrid aerogel according to claim 1, characterized in that: In step S1, the mass ratio of cellulose to vermiculite is (5-8):(1-4).
3. The method for preparing the cellulose hybrid aerogel according to claim 1 or 2, characterized in that: The agricultural solid waste is selected from any one of rice straw, stalks, corn cobs or bagasse.
4. The method for preparing the cellulose hybrid aerogel according to claim 1, characterized in that: In step S1, the process of extracting cellulose from agricultural solid waste includes: 1) crushing agricultural solid waste into 50-200 meshes, placing it in a mixed aqueous solution containing sodium chlorite and glacial acetic acid, and performing acid treatment at 70-90°C; 2) The material treated in step 1) is washed with water until the pH value is neutral, then placed in a sodium hydroxide solution, treated with alkali at 60-80° C., washed and dried to obtain cellulose powder.
5. The method for preparing cellulose hybrid aerogel according to claim 1, characterized in that: In step S1, the components of the alkaline urea solution include: 5-10 wt % of sodium hydroxide and 10-14 wt % of urea.
6. The method for preparing the cellulose hybrid aerogel according to claim 1 or 5, characterized in that: The solid-to-liquid ratio of the cellulose to the alkaline urea solution is 20-32 g / L.
7. The method for preparing cellulose hybrid aerogel according to claim 1, characterized in that: In step S2, the cross-linking agent is epichlorohydrin or glutaraldehyde.
8. The method for preparing cellulose hybrid aerogel according to claim 1, characterized in that: Step S1 also includes pre-treatment of the vermiculite, which includes: sequentially subjecting the vermiculite to acid treatment and homogenization treatment, and obtaining a vermiculite with an average particle size of 10 to 20 μm.
9. A cellulose hybrid aerogel, characterized in that: The cellulose hybrid aerogel is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the cellulose hybrid aerogel according to claim 9 in adsorbing microplastics in water.
Citation Information
Patent Citations
Method for preparing cellulose carbon aerogel from agricultural waste
CN108557802A
Cellulose / magnesium-aluminum layered bimetallic oxide aerogel as well as preparation method and application thereof
CN113617302A
Cellulose composite aerogel as well as preparation method and application thereof
CN116023715A
Preparation and application of composite aerogel material for removing micro-plastics in water body
CN117398976A
Preparation method of waste straw-based cellulose aerogel oil absorbent
CN117504827A
Cited By
Functionalized magnetic cellulose aerogel as well as preparation method and application thereof
CN120504879A
Biomass fiber aerogel for micro-plastic adsorption and preparation method thereof
CN120771800A
Multilayer biomass cellulose adsorption material as well as preparation method and application thereof
CN121988305A
A multi-layer biomass cellulose adsorption material, a preparation method and application thereof
CN121988305B
Cellulose-based aerogel containing quaternary ammonium salt modified cellulose derivative as well as preparation method and application of cellulose-based aerogel
CN122647772A
